2018
DOI: 10.1111/pde.13703
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pediatric alopecia areata with anthralin: A retrospective study of 37 patients

Abstract: Background/ObjectivesData on treatment options in pediatric alopecia areata are limited. Topical anthralin has been demonstrated to be an effective treatment option in adults and has minimal systemic toxicity. Prior results on its efficacy in children with alopecia areata have been mixed.MethodsMedical records of 37 patients with alopecia areata who were started on topical anthralin before age 17 were reviewed for efficacy and safety data. Scalp regrowth was quantified by serial photography if available or by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 18 publications
0
24
0
3
Order By: Relevance
“…HL is a symptom of a variety of several forms of alopecia, including AGA, AA, and telogen effluvium [110]. Recognized treatment involves the use of drugs that are effective only upon continued administration and are not free from side effects [110][111][112][113]. Some patients may find MXD use unhandy or expensive.…”
Section: Discussionmentioning
confidence: 99%
“…HL is a symptom of a variety of several forms of alopecia, including AGA, AA, and telogen effluvium [110]. Recognized treatment involves the use of drugs that are effective only upon continued administration and are not free from side effects [110][111][112][113]. Some patients may find MXD use unhandy or expensive.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) Reversible hemolytic anemia is the unique adverse effect observed with ribavirin treatment, in contrast to the cytotoxic effects that other molecules, such as thioguanine and avermectin B1, may have on human cells due to their nonselective activities (10,11). (v) Ribavirin can be administered orally (as a capsule or tablet), intravenously, or through inhalation (9), while only topical application is possible for some molecules, such as anthralin (12). That is why, in this study, a large panel of 100 Candida sp.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of its efficacy for AA is restricted to a small number of case series with inadequate controls. 60,61 Studies have suggested that anthralin may be effective high concentrations (0.5 or 1% cream) applied for short periods (20 to 30 minutes daily) on the alopecic scalp, in the so-called short-contact therapy. the time of contact is increased by 10 minutes every two weeks up to one hour or to the time required to produce a mild dermatitis.…”
Section: Topical Anthralinmentioning
confidence: 99%